Discovery and Characterization of 2-Aminooxazolines as Highly Potent, Selective, and Orally Active TAAR1 Agonists - Galley, Guido (ACS Med Chem Lett, 2015)
[Image: see text] 2-Aminooxazolines were discovered as a novel structural class of TAAR1 ligands. Starting from a known adrenergic compound 1, structural modifications were made to obtain highly potent and selective TAAR1 ligands such as 12 (RO5166017), 18 (RO5256390), 36 (RO5203648), and 48 (RO5263397). These compounds exhibit drug-like physicochemical properties, have good oral bioavailability, and display in vivo activity in a variety of animal models relevant for psychiatric diseases and addiction.